Pengaruh Penggunaan Media Accountpoly terhadap Keaktifan dan Motivasi Siswa pada Pembelajaran Siklus Akuntansi Perusahaan Jasa - Karina Ziza Sustanto; Jihan Ghefira Shadiq; Sulastri (FKIP, Universitas Banten Jaya, 2026)
Student-centered learning requires instructional media that actively engage students and enhance their motivation, particularly in accounting education where learning activities are often perceived as difficult and monotonous. At SMK Negeri 12 Malang, students demonstrated low learning activeness and insufficient learning motivation during the Service Company Accounting Cycle lessons, indicating the need for a more interactive learning medium. This study aimed to examine the effect of Accountpoly, a monopoly-inspired board game, on students' learning activeness and learning motivation. A quantitative pre-experimental study employing a One-Group Pretest–Posttest Design was conducted with two independent sample groups consisting of 60 tenth-grade accounting students: 30 students from Class X AK 2 were assessed for learning activeness, while 30 students from Class X AK 4 were assessed for learning motivation. Data were collected using Likert-scale questionnaires and analyzed through descriptive statistics, the Shapiro–Wilk normality test, paired-sample t-test, and N-Gain analysis. The findings showed that Accountpoly significantly improved learning activeness, with the mean score increasing from 30.83 to 40.20 (t = −7.913, p < .05) and a moderate N-Gain of 0.4508. Learning motivation also increased significantly, from 69.57 to 88.13 (t = −5.491, p < .001), although the N-Gain (0.1778) was categorized as low due to the high initial motivation scores. These findings indicate that Accountpoly is an effective game-based learning medium for promoting students' active participation and enhancing learning motivation in accounting education.